PENGARUH PENGGUNAAN MEDIA RODA PUTAR DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYYAH PADA ANAK DI TK ABA 14 SIDOKUMPUL KOTA LAMONGAN - Maulidyah, Unzilatul Fithri (Jurnal Penelitian Anak Usia Dini, 2024)
This research focuses on efforts to improve children's ability to recognize hijaiyyah letters through the use of spinning wheel media at Kindergarten ABA 14 Sidokumpul. With a sample size of 30 children who showed difficulty in recognizing these letters, researchers used a pre-experimental design (one group pre-post test design) to evaluate the effectiveness of the media used.The results of the research showed that the use of spinning wheel media succeeded in increasing children's ability to recognize hijaiyyah letters. The observations and treatment carried out showed significant improvement, with the average pretest score increasing from 16.4 to 20.7 after the intervention. Data analysis also shows high significance (0.000 < 0.05), which supports the hypothesis that the spinning wheel media has a positive effect on learning hijaiyyah letters.Researchers hope that the results of this research can become a reference for further research, especially in examining the long-term impact of introducing hijaiyyah letters on children's reading and writing abilities in the future.